Analisis Kemampuan Menyelesaikan Soal Cerita Materi Luas Bangun Datar Kelas IVB SDN Bandungan - Anita, Titin Dwi; Miyono, Noor (LPPM Institut Pendidikan Nusantara Global, 2024)
The culture of mathematical literacy in Indonesia is relatively low. One of the factors contributing to this low literacy rate is the lack of interest in reading among the population. A person's literacy is related to their critical thinking skills. Mathematical literacy is closely related to mathematics, as it involves the ability to reason critically using mathematical language and symbols. The purpose of this study is to analyze the mathematical literacy skills of fourth-grade students, involving three students from SDN Bendungan Semarang. The research instruments used were interviews and the results of students' worksheets in the form of mathematical word problems to analyze their mathematical literacy skills. Based on the research results from the three students with high, medium, and low abilities, it was found that all three students still have relatively low mathematical literacy skills. Additionally, students with high abilities do not necessarily have high mathematical literacy, and vice versa. Therefore, the role of the teacher is crucial in efforts to improve students' mathematical literacy skills by regularly providing problems that contain components of mathematical literacy.